MODEL KEWIRAUSAHAAN SEKOLAH (SCHOOL-BASED ENTERPRISE) SEBAGAI STRATEGI ALTERNATIF PEMBIAYAAN PENDIDIKAN DALAM RANGKA PENINGKATAN MUTU PEMBELAJARAN DI SDN 05 KABUNAN - Saputro Nugroho; Iskak Suparno; Sutrisno Sutrisno (Jurnal Manajemen Pendidikan, 2026)
Objective: This study aims to analyze the model of School-Based Enterprise (SBE) as an alternative financing strategy for education in improving the quality of learning at SDN 05 Kabunan. The limited dependence on government funding through the School Operational Assistance (BOS) has encouraged schools to develop entrepreneurial initiatives that can generate additional income independently. Methods: This research uses a qualitative approach with a case study method. Data were collected through in-depth interviews with the principal, teachers, school committee, and parents; non-participatory observation; and document analysis. Data validity was tested using source and technique triangulation. Data analysis used the Miles and Huberman interactive model which includes data reduction, data presentation, and conclusion drawing. Results: The results showed that SDN 05 Kabunan had developed three main School-Based Enterprise units, namely: (1) a school canteen managed collaboratively, (2) a plant nursery unit that functions as a learning medium and a source of income, and (3) a creative skills product sales unit. The proceeds from these three units have been able to contribute to school financing by an average of 18.7% per year, which is allocated for improving learning facilities, purchasing additional teaching materials, and supporting extracurricular activities.